The Policy Integration Concept of The Mahram Relationship on Nurseling Study on Nurseling Practices in Semarang, Central Java-Indonesia - Muna Madrah; Andi Riansyah; Alamsyah Alamsyah; Dewi Ayu Fatmawati; Badieah (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
Giving breast milk is becoming more popular, whether directly or mediated by organizations supporting nursing donors. In Muslim communities, donating breast milk has implications for the relationship between the child and the nursing mother, including the mother's husband and biological children. The relationship is called the mahram relationship. Mahram in Islam is essential because it clarifies the child's lineage and the relationship between the family of the nursing mother. The objectives of this study are 1). to describe the breastfeeding donor in Semarang; 2). to describe community awareness of its implication; and 3). questions whether any policy regulates the recording of breastfeeding donor practices to track mahram relationships. This is qualitative research by exploring information from primary sources in Semarang District. Furthermore, the data, also, is gathered from relevant policy documents to strengthen argumentation and analysis. The results indicate that breastfeeding donor policies already exist in Semarang, but each institution associated with various policies moves independently in its implementation. There is no policy regarding recording the mahram relations. The absence of a clear and integrated policy has led to a tendency for people to practice breastfeeding independently without the need to carry out official recording procedures. The research offers a cross-sectoral integrated policy concept aiming to fulfill children's rights to the best food in their early life while having the right to know the clarity of their lineage.